Water accounting : international approaches to policy and decision-making - Godfrey, Jayne M. (Jayne Maree).; Chalmers, Keryn, 1961- (Cheltenham, UK : Edward Elgar, 2012)
One of the most pressing global issues of the 21st Century is the scarcity of water of a quantity appropriate to ensure economic, environmental and social sustainability. In addressing the issue through policy and management, of critical importance is access to high quality information. JM Godfrey, ANU and K Chalmers, Monash Uni.
Two perspectives of water resource accounting : comparing the Australian and the United Nations approaches / Eric Mungatana and Rashid Hassan -- pt. III. Contemporary issues addressed by water accounting. The impossible planetary trust : intergenerational equity, long-term investment and water governance and regulation / Gordon L. Clark and Claire Woods -- Water accounting, corporate sustainability and the public interest / Mike Muller -- Water accounting and conflict mitigation / Lise Pretorius and Anthony Turton -- The role of a water accounting system in the avoidance and resolution of international water disputes / Andrew Allan -- Water accounting issues in California / Jay R. Lund -- Accounting for water rights in the western United States / Mark Squillace.
Includes bibliographical references and index.
Keywords: Water resources development -- Management; Water-supply -- Accounting; Water consumption -- Economic aspects; Water-supply -- Government policy